Par kursismiem mantāt un ramīt - Laumane, Benita (Baltistica, 2000)
On the couronisms mantāt and rāmītThe article deals with some words which are rarely encountered in Courland sub-dialects or in Latvian lexicographical sources. They could be relicts of the Couronian language and they have parallels in the Lithuanian language. Cf. the Latvian dialect word mañtāt (apmantāt, nuomantāt, piemantāt, samantāt) ‘to practice magic for protection; to charm away’ and the Lithuanian dialect word mántauti, mántoti, mántavoti ‘to heal’; the Latvian dialect word rāmīt (apramīt, paramīt) ‘to bury; to dig’ and the Lithuanian – ramìnti ‘to console’, dial. ramė́ti ‘to calm down’.
Keywords: latviešu valoda; leksikoloģija